2023
DOI: 10.1177/09504222231199989
|View full text |Cite
|
Sign up to set email alerts
|

Discussing ChatGPT’s implications for industry and higher education: The case for transdisciplinarity and digital humanities

Vera G. Dianova,
Mario D. Schultz

Abstract: This comment builds on the example of chat generative pretrained transformer (ChatGPT) to discuss the implications of generative AI on industry and higher education, underlining the need for more transdisciplinary digital literacy education. The release of ChatGPT has generated significant academic and professional interest and instigated a vibrant discussion on the opportunities offered and challenges posed by powerful and readily accessible generative AI reshaping teaching and learning at universities. ChatG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 64 publications
(83 reference statements)
0
0
0
Order By: Relevance
“…Kohnke et al (2023) introduced particular manifestations of digital competence essential for utilizing ChatGPT, underscoring the significance of social awareness. Another study underscored the necessity to cultivate interdisciplinary digital literacy in higher education, emphasizing comprehensive knowledge and adaptability (Dianova & Schultz, 2023). Johinke et al (2023) suggested that AI-driven text generators, like ChatGPT, had emerged through applications, potentially reshaping the landscape of digital literacy once more.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Kohnke et al (2023) introduced particular manifestations of digital competence essential for utilizing ChatGPT, underscoring the significance of social awareness. Another study underscored the necessity to cultivate interdisciplinary digital literacy in higher education, emphasizing comprehensive knowledge and adaptability (Dianova & Schultz, 2023). Johinke et al (2023) suggested that AI-driven text generators, like ChatGPT, had emerged through applications, potentially reshaping the landscape of digital literacy once more.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, many studies emphasized that the importance of digital literacy in universities was to encourage critical thinking and to realize ethical issues (Dianova & Schultz, 2023). The arise of artificial intelligence-based chatbots, such as ChatGPT, contributed to advancements in traditional education to give priority to critical thinking (Munoz-Basols et al, 2023).…”
Section: Rq4:could Digital Literacy Positively Influence Learners' Ou...mentioning
confidence: 99%